Inclusive Academic Practices in the University Classroom: Interchangeable Learning - Cubero Vásquez, Karol Viviana (2013)
In our university classrooms, there is an imperative need for implementing new educational practices that allow all students to participate actively and equally in the learning process. A change is required in the teaching-learning methodology to assure a more cooperative, inclusive, dynamic, and fair learning process based on by team work and peer support with tutoring given by students to their classmates. This practice not only benefits the student facing some difficulties, who learns with the support of one of his/her classmate but also  brings advantages to the student that teaches because with this, knowledge is reinforced, and thus when he or she teaches, he or she learns. When this practice is promoted, values such as solidarity, cooperation, responsibility, harmony, and friendship are shared among all the participants involved in the process. This article supports a cooperative learning process enriched with activities that value team work and tutoring among students, seeking a significant, effective, and interactive learning process that can lead to a more integral education of the learner.